Dysregulation of sterol regulatory element binding protein–1c in livers of morbidly obese women is associated with altered suppressor of cytokine signaling–3 and signal transducer and activator of transcription–1 signaling - Elam, Marshall B.; Yellaturu, Chandrahasa; Howell, George E.; Deng, Xiong; Cowan, George S.; Kumar, Poonam; Park, Edwards A.; Hiler, M. Lloyd; Wilcox, Henry G.; Hughes, Thomas A.; Cook, George A.; Raghow, Rajendra (Metabolism, clinical and experimental, 2010)
We compared hepatic expression of genes that regulate lipid biosynthesis and metabolic signaling in liver biopsy specimens from women who were undergoing gastric bypass surgery (GBP) for morbid obesity with that in women undergoing ventral hernia repair who had experienced massive weight loss (MWL) after prior GBP. Comprehensive metabolic profiles of morbidly obese (MO) (22 subjects) and MWL (9 subjects) were also compared. Analyses of gene expression in liver biopsies from MO and MWL were accomplished by Affymetrix microarray, real-time polymerase chain reaction, and Western blotting techniques. After GBP, MWL subjects had lost on average 102 lb as compared with MO subjects. This was accompanied by effective reversal of the dyslipidemia and insulin resistance that were present in MO. As compared with MWL, livers of MO subjects exhibited increased expression of sterol regulatory element binding protein (SREBP)–1c and its downstream lipogenic targets, fatty acid synthase and acetyl-coenzyme A-carboxylase–1. Livers of MO subjects also exhibited enhanced expression of suppressor of cytokine signaling–3 protein and attenuated Janus kinase signal transducer and activator of transcription (JAK/STAT) signaling. Consistent with these findings, we found that the human SREBP-1c promoter was positively regulated by insulin and negatively regulated by STAT3. These data support the hypothesis that suppressor of cytokine signaling–3–mediated attenuation of the STAT signaling pathway and resulting enhanced expression of SREBP-1c, a key regulator of de novo lipid biosynthesis, are mechanistically related to the development of hepatic insulin resistance and dyslipidemia in MO women.